Small bowel carcinoid: Location isn’t everything! - Hari, Danielle M (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate the prognostic significance of the primary site of disease for small bowel carcinoid (SBC) using a population-based analysis. METHODS: The Surveillance, Epidemiology and End Results (SEER) database was queried for histologically confirmed SBC between the years 1988 and 2009. Overall survival (OS) and disease-specific survival (DSS) were analyzed using the Kaplan-Meier method and compared using Log rank testing. Log rank and multivariate Cox regression analyses were used to identify predictors of survival using age, year of diagnosis, race, gender, tumor histology/size/location, tumor-node-metastasis stage, number of lymph nodes (LNs) examined and percent of LNs with metastases. RESULTS: Of the 3763 patients, 51.2% were male with a mean age of 62.13 years. Median follow-up was 50 mo. The 10-year OS and DSS for duodenal primaries were significantly better when compared to jejunal and ileal primaries (P = 0.02 and < 0.0001, respectively). On multivariate Cox regression analysis, after adjusting for multiple factors, primary site location was not a significant predictor of survival (P = 0.752 for OS and P = 0.966 DSS) while age, number of primaries, number of LNs examined, T-stage and M-stage were independent predictors of survival. CONCLUSION: This 21-year, population-based study of SBC challenges the concept that location of the primary lesion alone is a significant predictor of survival.